2011
DOI: 10.1177/147323001103900336
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Coronary Artery Calcification and Some Coronary Artery Calcification Risk Factors in Patients on Haemodialysis and in Patients with Type 2 Diabetes

Abstract: Patients on haemodialysis (HD) and patients with type 2 diabetes are at high-risk for coronary artery calcification (CAC). The coronary artery calcium score (CACS), quantified by computed tomography, cannot be completely explained by traditional cardiovascular disease risk factors. CAC was measured in 45 non-diabetic chronic kidney disease patients on HD and in 45 matched type 2 diabetes patients without diabetic nephropathy. Serum calcium, phosphate, 25-hydroxyvitamin D (25[OH]D), alkaline phosphatase, intact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Based on the categories of CACS which was defined in previous studies,[7] we selected CACS ≥80 which is considered as average risk of coronary artery events and higher.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the categories of CACS which was defined in previous studies,[7] we selected CACS ≥80 which is considered as average risk of coronary artery events and higher.…”
Section: Methodsmentioning
confidence: 99%
“…In a 10-year prospective study on 137 CKD patients, the authors found that severe CAC was an important predictor of cardiovascular mortality[ 151 ]. Krajnc et al [ 152 ] compared CAC score between patients on hemodialysis and diabetic patients without renal involvement and found higher CAC score in the hemodialysis group, with the difference between both groups especially evident in the very high risk CAC score category. Besides being an adverse prognostic sign, higher CAC has been associated with faster progression of CKD to ESRD[ 153 ].…”
Section: Imaging Techniquesmentioning
confidence: 99%